An Extended TPB Model to Predicting Consumer Acceptance Towards Remanufactured Goods: A case for Malaysia - Keong, Kenny Quah Chee; Kumar, Kavigtha Mohan; Abbasi, Ghazanfar A (Journal of Entrepreneurship, Business and Economics, 2020)
The purpose of this research is to unearth the factors which affect consumers attitude and their intention to purchase remanufactured goods in an emerging country like Malaysia. Thus, the proposed research model used in this study was grounded on the most frequently applied model, i.e. Theory of Planned Behaviour (TPB) and was further extended by integrating constructs like perceived knowledge, perceived risk and perceived benefit along with the original TPB constructs namely attitude, subjective norm and perceived behavioural control. The data was collected from 253 Malaysian consumers, primarily working adults with a steady income who have purchasing and absolute power over their choices of consumer electronics, specifically remanufactured products. The outcomes propose treasured understandings about the importance of studied constructs and how these constructs are indispensable in shaping positive behaviour towards acceptance of remanufactured products. Thereby, regulative bodies, remanufacturer, educators, government institutions, non-profit organizations and industry players could joint effort to raise awareness among Malaysian consumers towards sustainability and to encourage their attitude and behavioural intention towards remanufactured products. This research is one of the very few empirical researches endeavoured to evaluate Malaysian consumer’s attitude and purchase intention towards remanufactured products. Research paper Keywords: Theory of Planned Behaviour; Remanufactured goods; Attitude; Intention; Malaysia Reference to this paper should be made as follows: Keong, K. Q. C., Kumar, M. K., & Abbasi, G. A. (2020). An Extended TPB Model to Predicting Consumer Acceptance Towards Remanufactured Goods: A case for Malaysia, Journal of Entrepreneurship, Business and Economics , 8 (2), 93–119.